P10.05 Cost-effectiveness of screening for anal cancer using regular digital ano-rectal examinations in hiv-positive men who have sex with men. (13th September 2015) - Ong, J; Fairley, CK; Carroll, S; Walker, S; Chen, M; Read, T; Bradshaw, C; Grulich, A; Kaldor, J; Clarke, P
Abstract : Introduction: The optimal screening strategy for early anal cancer detection in men who have sex with men (MSM) living with HIV is unknown. Methods: We estimated the cost-effectiveness of regular anal examinations to screen for anal cancer in HIV-positive men MSM living in Australia using a probabilistic Markov model. Data sources were based on the medical literature and a clinical trial of HIV-positive MSM receiving an annual anal examination in Australia. The main outcome measures were undiscounted and discounted (at 3%) lifetime costs, life years gained, quality adjusted life years (QALY) gained and incremental cost-effectiveness ratio (ICER). Results: Base-case analysis estimated the average cost of screening for and management of anal cancer ranged from 195 for no screening to 1, 915 for lifetime annual screening of men aged ≥50 years. The incremental discounted, QALYs gained ranged from 0.02 for 4 yearly screening to 0.03 for annual screening of men aged ≥50 years. Screening of men aged ≥50 years generated ICERs of 29, 760 per QALY gained (for screening every 4 years), 32, 222 (every 3 years), and 45, 484 (every 2 years). Uncertainty for ICERs were most influenced by the cost (financially and decrease in quality of life) from a false positive result, specificity of the anal examination, the probability of detection outside a screening program and the discount rate. Conclusion: In settings where anal cytology for screening precursors of anal cancer is not available, screening for anal cancer by incorporating regular anal examinations into routine HIV care for MSM aged ≥50 years is most likely to be cost-effective by conventional standards. Disclosure of interest statement: This project was funded by a program grant from the Australian National Health and Medical Research Council.